Verbalno in posredno nasilje v urgentni dejavnosti - Jerkič, Karmen (Obzornik zdravstvene nege, 2014)
Introduction: The purpose of the research was to study the incidence of verbal and other forms of indirect violence on a sample of employees in nursing care in emergency services, namely: to identify the frequency of experiencing the violence, different forms, the most common perpetrators of verbal abuse, perceived causes and demographic variables of the employees in relation to a higher frequency of detection of violence at work. Methods: The study was conducted on a non-random sample of health care workers in the emergency departments on the primary and secondary health care level (n = 62). The questionnaire included 18 closed-ended questions. Data were described on the basis of the calculated frequencies, proportions and x2 test. Results: Two-thirds of the participants (46 responses or 74.2 %) had experienced verbal or other forms of indirect violence at the workplace, especially in the forms of verbal indirect active aggression from family members and patients. The most frequent reasons for abuse are: inadequate, overcrowded waiting rooms (36 responses). Senior nursing care workers (x2 = 9.841, p = 0.003) and older workers (x2 = 4.891, p = 0.041) are more likely to experience verbal and indirect forms of violence. Respondents perceive that the levels of verbal and indirect violence have moderately to markedly increased over the years. Discussion and conclusion: The results obtained are comparable with the results of studies abroad. Further studies of workplace violence should focus more on the detailed phenomenological experience of victims.
Keywords: emergency departments; nursing care; psihično nasilje; psychological violence; urgentne ambulante; zdravstvena nega